Systematic evaluation of mechanistic data in assessing in utero exposures to trichloroethylene and development of congenital heart defects. (30th April 2020) - Urban, Jonathan D.; Wikoff, Daniele S.; Chappell, Grace A.; Harris, Craig; Haws, Laurie C.
Abstract: The hypothesis that in utero exposures to low levels of trichloroethylene (TCE) may increase the risk of congenital heart defects (CHDs) in offspring remains a subject of substantial controversy within the scientific community due primarily to the reliance on an inconsistent and unreproducible experimental study in rats. To build on previous assessments that have primarily focused on epidemiological and experimental animal studies in developing conclusions, the objective of the current study is to conduct a systematic evaluation of mechanistic data related to in utero exposures to TCE and the development of CHDs. The evidence base was heterogeneous; 79 mechanistic datasets were identified, characterizing endpoints which ranged from molecular to organismal responses in seven species, involving both in vivo and in vitro study designs in mammalian and non-mammalian models. Of these, 24 datasets were considered reliable following critical appraisal using a study quality tool that employs metrics specific to the study type. Subsequent synthesis and integration demonstrated that the available mechanistic data: 1) did not support the potential for CHD hazard in humans, 2) did not support the biological plausibility of a response in humans based on organization via a putative adverse outcome pathway for valvulo-septal cardiac defects, and 3) were not suitable for serving as candidate studies in risk assessment. Findings supportive of an association were generally limited to in ovo chicken studies, in which TCE was administered in high concentration solutions via direct injection. Results of these in ovo studies were difficult to interpret for human health risk assessment given the lack of generalizability of the study models (including dose relevance, species-specific biological differences, variations in the construct of the study design, etc.). When the mechanistic data are integrated with findings from previous evaluations of human and animal evidence streams, the totality of evidence does not support CHDs as a critical effect in TCE human health risk assessment.